PERLINDUNGAN HUKUM TERHADAP TENAGA KERJA YANG ADA HUBUNGAN KELUARGA DI TINJAU DARI DARI UNDANG-UNDANG NOMOR 13 TAHUN 2003 - Ida Bagus Martha Teja Agastya; Anak Agung Ayu Ngurah Tini Rusmini Gorda (Jurnal Aktual Justice, 2020)
Labor in Indonesia is one of the ways for the community to be able to obtain an economy and is an abundant human resource. Practically, the definition of labor and labor is only differentiated by age limits. A financial institution is also a business entity whose main assets are in the form of money and cashable assets such as movable and immovable objects. One form of the financial institution itself is a bank. A bank is a business entity that specifically operates in the financial sector, which is obtained from the owner of the bank and then distributed to the public by providing savings and loans or what is commonly known as credit loans in that way the community can improve their economy and life expectancy. Regarding marriage, in companies, both government and private companies, stipulate a clause that limits the right to enter into marriage between workers working in the company. Termination of employment on the grounds that there is a marriage bond between workers, which has been approved or has been signed at the time of signing the contract agreement before starting to work in a company.